Computer vision symptoms in people with and without neck pain. - Teo, Caleb; Giffard, Phoebe; Johnston, Venerina; Treleaven, Julia (Applied Ergonomics, 2019)
Background: Sixty-four to 90% of computer users experience symptoms of computer vision syndrome (CVS). People with CVS symptoms experience neck pain (NP), and people with NP can have visual symptoms.Objectives: (1) To examine differences in CVS symptoms in computer users with and without persistent NP. (2) To determine relationships between visual ergonomics, demographics, and CVS in those with and without persistent NP DESIGN: Comparative cross-sectional observational study METHOD: An online survey consisting of multiple questionnaires including the Computer Vision Syndrome Questionnaire (CVS-Q), Visual Symptoms Survey (VSS), and Convergence Insufficiency Symptoms Survey (CISS) was completed by 167 participants.Results: The persistent NP group had significantly higher CVS-Q, VSS, and CISS scores (p <0.01) compared to controls. No relationships were found between visual ergonomics, demographics, and visual symptoms in both groups.Conclusions: People with persitent NP are more likely to present with CVS than controls. Clinicians should consider assessing visual symptoms in people presenting with persisting NP.